EVALUASI PROGRAM FULL DAY SCHOOL TERHADAP KEGIATAN BELAJAR DI SD NU NAWA KARTIKA KUDUS - Veronica Ree’valent Rizang Sulistiyanto; Ajeng Ayu Kusumaningrum; Lu’lu’ul Maknun; Fina Fakhriyah; Erik Aditia Ismaya (JIP: Jurnal Ilmu Pendidikan, 2025)
The full-day school program is designed to extend students' learning time in order to optimize the learning process and the comprehensive development of competencies. The evaluation of the full day school program at SD NU Nawa Kartika needs to be conducted thoroughly to determine whether the program being implemented aligns with educational objectives. This research aims to evaluate the Full Day School program at SD NU Nawa Kartika using the CIPP evaluation model. Data collection techniques were carried out through questionnaires and interviews involving teachers and students as respondents to obtain a comprehensive picture of the program's implementation. Data analysis techniques were conducted quantitatively and qualitatively using Microsoft Excel, focusing on the program's effectiveness based on indicators of student engagement, learning quality, and stakeholder satisfaction. The evaluation results show that the Full Day School program at SD NU Nawa Kartika is running effectively, as reflected in the increased student participation, optimal management of learning time, and positive responses from all respondents. These findings indicate that the program is worth maintaining and can serve as a model for other elementary schools that wish to improve the quality of education through a full-day learning system.